Предмет: Алгебра,
автор: avostrecov
sin^2a - cos^2a + cos^4acos^2a -sin^2a+sin^4a
Ответы
Автор ответа:
0
(Sin²a - Cos²a + Cos⁴a) / (Cos²a - Sin²a + Sin⁴a) =
= [Sin²a - Cos²a*(1 - Cos²a)] / [Cos²a - Sin²a*(1 - Sin²a)] =
= (Sin²a - Cos²aSin²a) / (Cos²a - Sin²aCos²a) =
= [Sin²a(1 - Cos²a)] / [Cos²a(1 - Sin²a)] = Sin⁴a / Cos⁴a = tg⁴a
= [Sin²a - Cos²a*(1 - Cos²a)] / [Cos²a - Sin²a*(1 - Sin²a)] =
= (Sin²a - Cos²aSin²a) / (Cos²a - Sin²aCos²a) =
= [Sin²a(1 - Cos²a)] / [Cos²a(1 - Sin²a)] = Sin⁴a / Cos⁴a = tg⁴a
Похожие вопросы
Предмет: Қазақ тiлi,
автор: ruslanandrejkin
Предмет: Физика,
автор: Natalya06072004
Предмет: Другие предметы,
автор: dakon627
Предмет: История,
автор: Устал